Effect of 1-MCP Combined with Controlled Atmosphere Preservation on the Storage Quality of Freshly Cut Capsicum frutescens - Lili ZHAO; Yiqing LI; Mengyao XU; Zhenyi CHEN; Guanying SHI; Le ZHANG; Pengfei JIANG; Yuting SHI; Zhenwei CHEN; Zhaogai WANG (Shipin gongye ke-ji)
In order to extend the shelf life of fresh cut Capsicum frutescens, the effects of 1-methylcyclopropene (1-MCP) combined with controlled atmosphere storage (CA) on the quality of fresh cut Capsicum frutescens were investigated by measuring the changes of sensory quality, weight loss rate, decay rate, color, hardness, soluble solids, vitamin C, malondialdehyde content, ethylene generation rate, total bacterial count, and volatile components during storage. The results showed that the 1-MCP combined with controlled atmosphere (1-MCP+CA) storage could retain good appearance quality after 15 days of storage, while the control group showed browning and softening on the 6th day. In addition, the VC and soluble solids content of fresh cut Capsicum frutescens in 1-MCP+CA group were 1.35 and 1.81 times higher than those in CK group (P<0.05). At the end of storage, the 1-MCP+CA group could reduce weight loss rate by 6.75% and decay rate by 2.31%, inhibit the increase of malondialdehyde content and reduce ethylene production rate (P<0.05). The total bacterial count (3.15 lg (CFU/g)) was significantly lower than that of the CK group (6.42 lg (CFU/g)) (P<0.05). GC-IMS identified a total of 34 volatile compounds, including 8 alcohols, 5 aldehydes, 2 terpenes, 7 ketones, 5 esters, 2 acids, 3 heterocycles, and 2 other compounds. As the storage period extended to 6 days, 1-MCP+CA treatment had no significant effect on volatile compounds such as ketones, alcohols, aldehydes, esters, and acids with relatively high content in the fresh cut Capsicum frutescens (P>0.05), which could better maintain the characteristic flavor components of fresh cut Capsicum frutescens and extend their shelf life. This study provides theoretical reference and technical support for the preservation and storage of fresh cut vegetables.